2013
DOI: 10.1111/tpj.12301
|View full text |Cite
|
Sign up to set email alerts
|

‘Real time’ genetic manipulation: a new tool for ecological field studies

Abstract: SUMMARYField experiments with transgenic plants often reveal the functional significance of genetic traits that are important for the performance of the plants in their natural environments. Until now, only constitutive overexpression, ectopic expression and gene silencing methods have been used to analyze gene-related phenotypes in natural habitats. These methods do not allow sufficient control over gene expression for the study of ecological interactions in real time, of genetic traits that play essential ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 74 publications
0
53
0
Order By: Relevance
“…However, legumes do contain significant concentrations of phytoestrogens which may be responsible for the expression from the pER8 promoter in Medicago. As observed in the above ground parts of Arabidopsis and tobacco, neither dexamethasone nor estradiol appeared to have effect on the growth of transgenic Medicago roots31011.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, legumes do contain significant concentrations of phytoestrogens which may be responsible for the expression from the pER8 promoter in Medicago. As observed in the above ground parts of Arabidopsis and tobacco, neither dexamethasone nor estradiol appeared to have effect on the growth of transgenic Medicago roots31011.…”
Section: Discussionmentioning
confidence: 62%
“…Although the application of dexamethasone system has been reported in leaves3, flowers3 and seeds10, less has been described on application of the inducible silencing systems in roots. Our data provided original quantitative analyses on how this chemically inducible system can silence genes in a temporal and dose-dependent manner in roots and demonstrated how a lethal gene could be chemically silenced and the resultant phenotypes illustrated in roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial attempts to create transgenic, dexamethasone-inducible plants (Schäfer et al, 2013) harboring a silencing construct for the IAA receptor TIR1 failed, either because of promoter methylation in the F2 crosses (Weinhold et al, 2013) or because the identified TIR1 homolog was inactive. We therefore took advantage of our knowledge on systemic IAA accumulation to devise a series of chemical manipulation experiments.…”
Section: Sexta-induced Iaa Is Required For the Induction Of Anthocmentioning
confidence: 99%
“…Once candidate genes have been identified by genetic mapping, they can be validated through knockdown by RNA interference, overexpression, or targeted modification of the genome sequences in the organisms of interest (Kang and Baldwin 2008). This approach has translated successfully to field experiments on chemically mediated plant defense and reproductive ecology in wild tobacco (Nicotiana attenuata) (Baldwin 2010, Scha¨fer et al 2013). An additional benefit of such studies is that selective trait-silencing may reveal unexpected ecological interactions that are preempted by wild-type trait expression.…”
Section: Box 2: Information Landscapes and Community Dynamicsmentioning
confidence: 99%